Translocality/Methodology. The Americas, or Experiencing the World - Jędrzejko, Paweł (Review of International American Studies, 2020)
The Americas offer a peculiar stage for translocal methodologies. If we agree that the products of Chinese American culture—which, in the course of the last 170 years of interaction, has evolved into a unique, American, phenomenon—can not be labeled as “Made in China,” then contemporary Chinese medicine in the Americas cannot legitimately be perceived solely as an ‘import.’ Beyond doubt, phenomena such as the emergence of the American College of Traditional Chinese Medicine at the California Institute of Integral Studies testify to the fact that the once ‘exotic’ forms of therapy are now being granted a status parallel to those developed throughout the history of Western medicine. Increasingly, as translocal, they are becoming recognized as non-foreign elements of the glocal culture. Similarly, the exploration of the physical world, which, to an experienced dancer of Bharatanatyam, Odissi, or any other of the dominant forms of the classical Indian dance is an obvious function of his or her own experience of the ‘body-in-the-world,’ has, translocally, opened up an altogether new space of profound understanding of ourselves in our environment. It is not about the fashionable, politically correct, ‘openness to other cultures’; it is about the opening up to a parallel meditative experience of the “bodymind,” which neither excludes nor isolates the sphere of emotions from the reality of what-is-being-experienced. Or, to express it in terms more easily comprehensible to a Western reader, dance may prove to be a methodology (not just a method) serving the purpose of a more profound understanding of the complexity and unity of the universe, and a language to express this understanding. Making the most of available traditions might produce much greater benefits than remaining locked within just one, Western, Anglonormative, library of concepts. In the context of the ongoing debate on transnational American Studies, the article offers an insight into how the worldwide studies of the Americas and translocality intersect, and how such a perspective may contribute to the multifaceted process of the decolonization, understood both literally and intellectually.